Types of Control of Biological Drives - P. A. Sorokin (Концепт: философия, религия, культура, 2022)
Here we present the translation of Chapter 15 Types of Control of Biological Drives of the work The Ways and Power of Love: Types, Factors, and Techniques of Moral Transformation by Pitirim A. Sorokin, an outstanding American sociologist and philosopher of Russian origin. Sorokin’s notes translated from the original text are presented in the footnotes, the references in English are given in the Author’s spelling. The Ways and Power of Love: Types, Factors, and Techniques of Moral Transformation represent an example of late writings of Pitirim Sorokin when he lived in the USA, leading one of the Harvard Research Centers. The first edition of the book was first published in 1954. His sons initiated an extended edition of Sorokin’s work in 1982. This translation based on the publication brought back into print in 2002 allows a new generation of readers to acquaint themselves with the work of a distinguished thinker. His late work is a pioneering endeavor of considering love in its multiple forms at the intersection of science and religion. We chose to offer a translation of Chapter 15 as the most interesting from the point of view of philosophy, cultural and religious studies. Herein P. Sorokin considers the interconnection of religious practices of curbing passions and provides a critical analysis and comparison of multiple approached to holding back the flesh as an attempt to attain a valuable result from ethical and religious perspective.